2013
DOI: 10.1590/s1413-35552012005000074
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of isokinetic evaluation in passive mode for knee flexors and extensors in healthy children

Abstract: | Background: The isokinetic dynamometer has been considered the gold-standard measurement of muscle performance. However, the reliability for the passive mode in children has not been reported to date. Objectives: The purpose was to evaluate the reliability of the isokinetic dynamometer in passive mode in children. Method: Twenty-one healthy children (ten girls, eleven boys), aged 5 to 12 years (age: 8.5±2.2 years), were evaluated using an isokinetic dynamometer. Each participant was tested twice with a one-w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
27
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 43 publications
7
27
2
Order By: Relevance
“…The magnitude of the ICCs for isokinetic knee extension and flexion torque in our study are comparable to earlier studies on children [7,14,28], although somewhat lower than reported in adults (0.85 to 0.94) [10,30].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The magnitude of the ICCs for isokinetic knee extension and flexion torque in our study are comparable to earlier studies on children [7,14,28], although somewhat lower than reported in adults (0.85 to 0.94) [10,30].…”
Section: Discussionsupporting
confidence: 90%
“…This indicates that our SEM% values are comparable to previous results in children [7,16,18,28]. Our SRD% values suggest that a change above 14% to 16% for knee extension and 22% to 25% for flexion is necessary to reflect a real change in knee function.…”
Section: Discussionsupporting
confidence: 89%
“…However, the size of the testing sample is comparable to the ones reported by other research papers on reliability in healthy adults [7,10]. Also, it should be borne in mind that the observed findings can be different from earlier findings reported for specific subjects, such as the elderly [17,29] or children [16,19]. Another limitation of the current study might be that only one testing velocity and the concentric mode of action was used for measurement of ankle INV/EV.…”
Section: Discussionsupporting
confidence: 74%
“…The studies’ results are, however, difficult to interpret and compare due to differences in testing protocols (e.g., testing position and stabilization, testing velocities and modes of muscle action, passive or active mode of testing, gravitational correction application, testing bare feet or with shoes, etc.) [5,7,15,16]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation